1995
DOI: 10.1126/science.270.5243.1821
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the V α Domain of a T Cell Antigen Receptor

Abstract: The crystal structure of the V alpha domain of a T cell antigen receptor (TCR) was determined at a resolution of 2.2 angstroms. This structure represents an immunoglobulin topology set different from those previously described. A switch in a polypeptide strand from one beta sheet to the other enables a pair of V alpha homodimers to pack together to form a tetramer, such that the homodimers are parallel to each other and all hypervariable loops face in one direction. On the basis of the observed mode of V alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
3

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(120 citation statements)
references
References 36 publications
7
110
3
Order By: Relevance
“…Thus, CTL 121 expresses only one TCR. Taking into account the conserved conformation of the CDR1␣ loops that have been studied so far by crystallography (30), the CDR1␣ amino acid sequence of the TCR of CTL 121 was compared with the sequence of TCR A6 interacting with a tax peptide presented by HLA-A2. The crystal structure of this last TCR had revealed that it was the Q at position 30 of the CDR1␣ that interacts with a neutral G at position 4 of the peptide (31).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, CTL 121 expresses only one TCR. Taking into account the conserved conformation of the CDR1␣ loops that have been studied so far by crystallography (30), the CDR1␣ amino acid sequence of the TCR of CTL 121 was compared with the sequence of TCR A6 interacting with a tax peptide presented by HLA-A2. The crystal structure of this last TCR had revealed that it was the Q at position 30 of the CDR1␣ that interacts with a neutral G at position 4 of the peptide (31).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, crystallographical studies on a BV8S2A1 encoded TCR ␤ chain and an AV4S2 TCR ␣ chain fragment confirmed that TCR are folded in an Ig-like manner but also indicated significant structural differences, such as different hinge structures and interstrand hydrogen bond formation (4,5). Little is still known on how TCR bind their ligand (MHCpeptide complexes).…”
Section: From the ‡Ludwig Institute For Cancer Research Lausanne Bramentioning
confidence: 99%
“…Three complementarity-determining regions (CDR1, CDR2 and CDR3) have been defined for each of the two TCR chains. Although challenged by some recent studies [3][4][5][6], the portion of the TCR essentially responsible for interaction with the antigenic peptide has been claimed to lie in the CDR3 loops of the two variable regions [1,[7][8][9][10][11][12]. By definition, part of the CDR3 region is encoded by a given J gene segment [7].…”
Section: Introductionmentioning
confidence: 99%